2011
DOI: 10.1162/jocn_a_00095
|View full text |Cite
|
Sign up to set email alerts
|

TMS to the Lateral Occipital Cortex Disrupts Object Processing but Facilitates Scene Processing

Abstract: The study of brain-damaged patients and advancements in neuroimaging have lead to the discovery of discrete brain regions that process visual image categories, such as objects and scenes. However, how these visual image categories interact remains unclear. For example, is scene perception simply an extension of object perception, or can global scene "gist" be processed independently of its component objects? Specifically, when recognizing a scene such as an "office," does one need to first recognize its indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 48 publications
7
53
0
Order By: Relevance
“…This null result is not definitive and should be interpreted cautiously. Previous research has shown that object categorization can be impaired with TMS to area LO using a protocol similar to that in the current study (Mullin and Steeves, 2011). It is possible that face categorization could be impaired by TMS if one could access deeper brain structures in the face network, particularly the FFA.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This null result is not definitive and should be interpreted cautiously. Previous research has shown that object categorization can be impaired with TMS to area LO using a protocol similar to that in the current study (Mullin and Steeves, 2011). It is possible that face categorization could be impaired by TMS if one could access deeper brain structures in the face network, particularly the FFA.…”
Section: Discussionmentioning
confidence: 82%
“…TMS was delivered at 10 Hz and 60% of maximal stimulator output, similar to previous studies (e.g. Mullin & Steeves, 2011;Pitcher et al, 2007). The frequency, intensity and duration of the TMS train were well within the TMS safety limits (Wassermann, 1998;Rossi, Hallett, Rossini, & Pascual-Leone, 2009).…”
Section: Stimulation Parametersmentioning
confidence: 92%
See 1 more Smart Citation
“…Three TMS pulses were delivered at onset of each painting, given prior TMS evidence showing that contribution of LO to object processing takes place within the first 180 ms of stimulus onset (e.g. Mullin & Steeves, 2011), and that triple-pulse 10 Hz TMS has been used before to interfere with underlying cortical activity (e.g., Cohen Kadosh et al, 2007;see Bona, Herbert, Toneatto, Silvanto, & Cattaneo, 2014 for triple-pulse 10 Hz TMS over LO region). Stimulation order was counterbalanced across participants.…”
Section: Transcranial Magnetic Stimulationmentioning
confidence: 99%
“…As such, it is unsurprising that functional neuroimaging techniques have revealed a putative “core” scene processing network in the human brain that responds strongly when viewing navigationally relevant stimuli (e.g., scenes) versus other visual categories. This core network is thought to include posterior parahippocampal gyrus [PHG; Aguirre et al, 1998a; Epstein et al, 2003; Epstein and Kanwisher, 1998], retrosplenial cortex [RSC; Auger et al, 2012; Epstein et al, 2007; Vann et al, 2009] and the transverse occipital sulcus [TOS; Dilks et al, 2013; Ganaden et al, 2013; He et al, 2013; Mullin and Steeves, 2011; Nasr et al, 2011]. As seen in the neural processing of other visual categories [Taylor and Downing, 2011], these regions appear to support distinct but complementary aspects of scene processing, and are differentially modulated by changes in viewpoint [Epstein et al, 2003, 2007; Park and Chun, 2009], spatial layout [Harel et al, 2013; Park et al, 2015], and lower‐level spatial features [Kravitz et al, 2011a; Nasr et al, 2014].…”
Section: Introductionmentioning
confidence: 99%